Penerapan Sistem Informasi Manajemen dalam Meningkatkan Efisiensi Perusahaan - Indriani Azzahra; Rayyan Firdaus (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Management Information Systems (MIS) are an integral part of modern enterprise operations. This article discusses the application of SIM in improving company efficiency. This research uses a qualitative approach to analyze how SIM can optimize management processes, decision making, and operational control. The results show that effective implementation of SIM can help companies to increase productivity, reduce operational costs, and improve customer satisfaction. In addition, this article also discusses the challenges and barriers that may be faced in SIM implementation as well as strategies to overcome them.